2022
DOI: 10.3389/fpubh.2022.874741
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Anti-S1-RBD Antibodies in Pre-pandemic and Pandemic Subjects From Hail Region, KSA

Abstract: BackgroundTwo years into the pandemic, yet the threat of new SARS-CoV-2 variants continues to loom large. Sustained efforts are required to fully understand the infection in asymptomatic individuals and those with complications. Identification, containment, care, and preventative strategies rely on understanding the varied humoral immune responses.MethodsAn in-house ELISA was developed and standardized to screen for serum IgG antibodies against the SARS-CoV-2 S1-RBD protein as an antigen. This study aims to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…In this study, we found that several samples from the pre-pandemic era show high anti-RBD titers. Similar results have been reported by other studies, which suggested that the positivity shown by the samples from the pre-pandemic era might be due to cross-reactivity by previous infection with other coronaviruses, such as common cold-causing coronavirus [49,50].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found that several samples from the pre-pandemic era show high anti-RBD titers. Similar results have been reported by other studies, which suggested that the positivity shown by the samples from the pre-pandemic era might be due to cross-reactivity by previous infection with other coronaviruses, such as common cold-causing coronavirus [49,50].…”
Section: Discussionsupporting
confidence: 90%